Leo Panitch in full flight: on contradictions, polarizations, and socialist immortality. Issue 1 (2nd January 2021) - Gindin, Sam
Abstract: An elaboration on some of the issues addressed in "The growing contradictions within the Empire: An interview with Leo Panitch" by Ana Garcia, Debora Gaspar, and Filipe Mendonça, as well as on other topics, including the threat of fascism in the United States that Panitch was debating with close comrades in the last months of his life.